A minority within a minority: An exploration into the prevalence of neurodevelopmental disorders in looked after children and the effects on health and social wellbeing - NICOLA HEADY (2023)
Looked after children (Lac) continue to be one of the most vulnerable groups in society and many go on to attain poor health and social outcomes. Research on neurodevelopmental disorders (NDDs) in the general population is relatively well documented, however, research on Lac with NDDs is extremely limited. The aims of this thesis were to explore the prevalence of NDDs in the Lac population and if feasible compare rates to children who are not looked after (non-Lac). It further aimed to explore the impacts, challenges, barriers or wider factors that the Lac with a NDD might encounter or experience. To address the aims of this thesis, several methods have been used to collate data which are detailed in Chapters 2, 3, 4 and 5. Chapter 2 consists of a systematic review and meta-analysis which compares the prevalence of NDDs in Lac versus non-Lac and further explores the impacts on the Lac with a NDD. Twelve studies met eligibility. Six studies met eligibility for a meta-analysis and the remaining six studies are described as a narrative. In the review, there was a higher prevalence of ADHD and autism in the Lac population compared to their non-lac peers. The review also highlighted several adverse impacts and outcomes for the Lac with a NDD in the areas of care placement, criminal involvement, medication prescription, mental health services, emotional and physical abuse. Chapter 3 describes a brief narrative review which examines five studies that were not eligible for the systematic review but were important to further explore as they highlighted adverse impacts for the Lac with a NDD. This chapter examines these studies in more detail and relates the findings to wider literature. Similar adverse outcomes and impacts like those found in the systematic review were found but several additional adverse impacts and outcomes in areas of sexual abuse, homelessness, suicidal ideation, learning difficulties and physical health difficulties were also identified for the Lac with a NDD. As I could not interview Lac themselves, Chapter 4 describes a small q qualitative study, which was conducted to gain an insight into the perspectives and opinions of social workers on the little explored subject of NDDs in this population. Several broad topics were explored in areas of family, services and outcomes by means of interviews. Ten semi structured interviews were held, and a thematic analysis was utilised to analyse, code and identify themes. Themes involved perceptions of NDDs, perceptions of diagnosis, access to service provision, impact on care settings, impacts on health and social wellbeing, parental factors and social worker challenges and needs. Chapter five describes an electronic data linkage cohort study which investigates whether the prevalence rates attained from the meta-analysis for Lac reflect current prevalence estimates in Wales. It further examines whether there is similarity in several of the key findings detailed in the other chapters, in relation to services. Six health and administrative datasets held in the ‘Secured Anonymised Information Linkage (SAIL) databank at Swansea University were linked to explore and compare prevalence rates of NDDs and service usage in the Lac population compared to all children/young persons (Acyp) with a NDD in Wales. There was a higher prevalence of attention/deficit hyperactivity disorders, autistic spectrum disorders, developmental disorder of scholastic disorders, unspecified, eating disorders and reactive attachment disorders in Lac compared to Acyp in Wales. The results also highlight the mean age, gender of the first event/episode in which a NDD was identified within the dataset and the mean age, gender at time-of-service referrals to secondary health care services. In addition to this, results further highlight the educational support provision for both Lac and Acyp with a NND who have been placed in the ‘educated other than school’ (EOTAS) setting. The final chapter integrates all the findings of this thesis into a brief discussion and highlights any similarities, parallels, or ambiguities, followed by recommendations for research, policy and practice. My thesis proposes that more research is needed to support and understand the higher prevalence rates of NDDs in the already vulnerable Lac population. The identified impacts on the Lac with a NDD and the challenges, barriers and wider factors that these children may experience, or encounter may place these children at higher risk of adverse outcomes. More research in these areas would be beneficial to meeting the unique needs of the Lac with a NDD, particularly from a preventative and safeguarding perspective.